The adequacy of the international cooperation means for combating cybercrime and ways to modernize it - Al Azzam, Farouq Ahmad Faleh (2019)
The era of scientific and technological development has witnessed an extensive use of Internet and electronic devices in various aspects of life. This widespread use has increased security risks, privacy and cyberattacks that threaten both individuals and States. This kind of crime is difficult to prevent as a result of the constant digital technological advances and globalization. There is a growing concern among States and government agencies that such intrusions could critically affect the security and the economics of any State. Combating this kind of crime requires international cooperation. Therefore, many States have called for the need to define cybercrime and to hold conventions to adopt effective legal framework to combat and restrict the progress of cybercrime worldwide. This study concluded that cooperative mechanisms are needed to coordinate and unify joint efforts and to modernize means of combating cybercrime using the latest techniques. In addition, it is necessary to upgrade existing mechanisms and develop other methods to achieve various aspects of cooperation.